الجهود الدولية للحد من التغيير المناخي (Comprehensive Journal of Science, 2025)
This study aims to provide an integrated analysis of the causes and impacts of climate change and to evaluate the effectiveness of international efforts undertaken to mitigate this phenomenon over recent decades. The research adopted a descriptive-analytical methodology, involving a critical review of official scientific reports (such as those by IPCC and UNEP) and international legal documents (UNFCCC and the Paris Agreement), with the goal of determining the correlation between global commitments and actual emissions outcomes.The findings reveal the dominance of anthropogenic activities, particularly fossil fuel combustion, as the primary driver of warming, resulting in impacts that threaten food security and exacerbate climate displacement globally. On the diplomatic front, efforts successfully established a comprehensive framework through the Paris Agreement (2015), which set a 1.5°C limit and adopted the mechanism of Nationally Determined Contributions (NDCs). However, the assessment exposed a significant ambition gap, as current commitments suggest the world is on a trajectory for a temperature rise between 2.5°C and 2.9°C, substantially exceeding the safe threshold.This failure in implementation is attributed to structural challenges, including inadequate climate finance, weak voluntary oversight mechanisms, and the influence of political pressures from major corporations. The study concludes that current efforts are insufficient to avert the most dangerous consequences. Consequently, the study recommends the necessity of transitioning to stricter and more comprehensive national policies, coupled with enhanced funding and clean technology transfer, to bridge the gap between commitments and outcomes and achieve global climate stability.